Distribution of visual attention in the performance of a reading task with specialized long nominal syntagms (SNEE) - Rey Sánchez, Omar Alejandro (2023)
The main aim of this exploratory and pre-experimental study is to establish the variations in the distribution of visual attention of translators in training during a reading task with Specialized Extensive Nominal Phrases (hereinafter SNEE). To achieve this goal, a case study was conducted with four translators in training who had to read 10 contexts of a Human Genome corpus that contains SNEE of three and five tokens. Data collection was performed through the eye movement technique and a Likert scale-type questionnaire. The results of this study showed that the distribution of the visual attention of the translators in training presented variations according to the length of the SNEE. Longer  time and number of fixations were observed in the SNEE of five tokens in contrast to the SNEE of three tokens. Likewise, the length variable is a factor that affects visual attention during the performance of this reading task.